2015
DOI: 10.1177/0091415015616394
|View full text |Cite
|
Sign up to set email alerts
|

Gender as a Moderator of the Relation Between Age Cohort and Three-Dimensional Wisdom in Iranian Culture

Abstract: This study examined whether gender moderated the association between age cohort and the cognitive, reflective, and compassionate dimensions of wisdom, using an Iranian sample of 439 adults from three age cohorts: young (18-34), middle-aged (35-54), and older (55 and above). Results indicated that the interaction effect between gender and age cohort was significant for three-dimensional wisdom and all three wisdom dimensions. Compared with younger women and older men, older women tended to have less education a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 45 publications
0
13
1
Order By: Relevance
“…They try to gain life insights from these events and actively project them into a future life. However, Cheraghi et al (2015) obtained different results using 3D-WS. Specifically, they found that there were no significant differences between young men and women (aged 18–35 years) in the reflective dimension of 3D-WS.…”
Section: Gender and Wisdom Levelmentioning
confidence: 96%
See 2 more Smart Citations
“…They try to gain life insights from these events and actively project them into a future life. However, Cheraghi et al (2015) obtained different results using 3D-WS. Specifically, they found that there were no significant differences between young men and women (aged 18–35 years) in the reflective dimension of 3D-WS.…”
Section: Gender and Wisdom Levelmentioning
confidence: 96%
“…Although some empirical studies have found a significant relationship between overall wisdom and gender ( Ardelt and Jeste, 2018 ; Webster et al, 2018 ) and significant differences in wisdom levels between men and women ( Cheraghi et al, 2015 ; Huynh et al, 2017 ), most had a small effect size: the absolute value of r ranges from 0.062 to 0.291; the absolute value range of partial n 2 is 0.01 to 0.03. According to the judgment criteria for the magnitude of effect size proposed by Cohen (1988) , these results were not ideal, or their explanatory powers were limited (see Table 2 for further details).…”
Section: Gender and Wisdom Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Relevant evidence appears inconclusive. Some studies have reported close-to-zero correlations between wisdom and age across the lifespan (e.g., Cheraghi, Kadivar, Ardelt, Asgari, & Farzad, 2015;Grossmann & Kross, 2014;Grossmann, Oakes, & Santos, 2019;Levenson et al, 2005), whereas others have reported small-to-moderate negative correlations (e.g., Monika Ardelt & Jeste, 2016;Bang & Montgomery, 2013;Mansfield, McLean, & Lilgendahl, 2010), while still other studies have reported moderate-to-large correlations (e.g., Grossmann et al, 2010;Kunzmann & Baltes, 2003).…”
Section: Wisdom and Agingmentioning
confidence: 99%
“…The results showed that 5.85% of personal attributes (gender, age, ethnicity) and spiritual guidance contribute to wisdom according to the views of prospective Indonesian counselors. Empirical studies show that gender and age have a significant positive effect on overall wisdom and on the cognitive, reflective, and affective dimensions (Cheraghi, Kadivar, Ardelt, Asgari, & Farzad, 2015). Other studies (Hollingworth, Sánchez-Escobedo, Graudina, Misiuniene, & Park, 2013) indicated that gender contributes 52% to the variation in wisdom of adolescents aged 15-18 years in Latvia, Lithuania, Mexico, Korea, and the USA.…”
Section: Personal Attributesmentioning
confidence: 99%